Youths’ Educational Resilience in Rurban Jumla: A Narrative Inquiry - Gautam, Suresh (Journal of Education and Research, 2016)
Drawing on the concept of resilience, this paper discusses a narrative-based research which explores rural/urban disparities among young people who face various obstacles to continue their higher education in recently announced ‘urban’ Jumla. I explore major adversities faced by the youths in rural-urban disparities, their promotive and protective measures, and cultural and family assets to cope with adversities. The three narratives illustrate how the youths develop their assets to overcome geographical and social adversities in rural-urban disparities. In doing so, I mainly deal with the youths’ issues of higher education attainment. They experience that it has been more privileged living in urban than in rural areas to continue their higher education. However, they could not detach themselves from the rural values and tradition. I generate meaning of youths’ educational resilience that overcomes such rural urban disparities.